Combination of rRT-PCR and Clinical Features to Predict Coronavirus Disease 2019 for Nosocomial Infection Control - Yamaguchi F; Suzuki A; Hashiguchi M; Kondo E; Maeda A; Yokoe T; Sasaki J; Shikama Y; Hayashi M; Kobayashi S; Suzuki H (Infection and Drug Resistance, 2024)
Fumihiro Yamaguchi,1 Ayako Suzuki,2 Miyuki Hashiguchi,3 Emiko Kondo,3 Atsuo Maeda,4 Takuya Yokoe,1 Jun Sasaki,4 Yusuke Shikama,1 Munetaka Hayashi,4 Sei Kobayashi,5 Hiroshi Suzuki6 1Department of Respiratory Medicine, Showa University Fujigaoka Hospital, Yokohama, Japan; 2Department of Pharmacy, Showa University Fujigaoka Hospital, Yokohama, Japan; 3Department of Infection Control, Showa University Fujigaoka Hospital, Yokohama, Japan; 4Department of Emergency and Critical Care Medicine, Showa University Fujigaoka Hospital, Yokohama, Japan; 5Department of Otolaryngology, Showa University Fujigaoka Hospital, Yokohama, Japan; 6Department of Cardiology, Showa University Fujigaoka Hospital, Yokohama, JapanCorrespondence: Fumihiro Yamaguchi, Department of Respiratory Medicine, Showa University Fujigaoka Hospital, 1-30 Fujigaoka, Aoba-ku, Yokohama, 227-8501, Japan, Email f_y@med.showa-u.ac.jpBackground: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), immediately became a pandemic. Therefore, nosocomial infection control is necessary to screen for patients with possible COVID-19.Objective: This study aimed to investigate commonly measured clinical variables to predict COVID-19.Methods: This cross-sectional study enrolled 1087 patients in the isolation ward of a university hospital. Conferences were organized to differentiate COVID-19 from non-COVID-19 cases, and multiple nucleic acid tests were mandatory when COVID-19 could not be excluded. Multivariate logistic regression models were employed to determine the clinical factors associated with COVID-19 at the time of hospitalization.Results: Overall, 352 (32.4%) patients were diagnosed with COVID-19. The majority of the non-COVID-19 cases were predominantly caused by bacterial infections. Multivariate analysis indicated that COVID-19 was significantly associated with age, sex, body mass index, lactate dehydrogenase, C-reactive protein, and malignancy.Conclusion: Some clinical factors are useful to predict patients with COVID-19 among those with symptoms similar to COVID-19. This study suggests that at least two real-time reverse-transcription polymerase chain reactions of SARS-CoV-2 are recommended to exclude COVID-19.Keywords: severe acute respiratory syndrome coronavirus-2, coronavirus disease 2019, nosocomial infection control, nucleic acid test, obesity, cross sectional study, Japan